Evaluation of radiation protection conditions in intraoral radiology - Miguel,Cristiano (2016)
Abstract Introduction: The dental radiology represents about 20% of human exposure to radiation in radio diagnostic. Although the doses practiced in intraoral dentistry are considered low, they should not be ignored due to the volume of the performed procedures. This study presents the radiation protection conditions for intraoral radiology in Curitiba - PR. Methods Data was collected through a quantitative field research of a descriptive nature during the period between September of 2013 and December of 2014. The survey sample consisted of 97 dentists and 130 intraoral equipments. The data related to the equipments was collected using structured questions and quality control evaluations. The evaluations of the entrance skin dose, the size of the radiation field and the total filtration were performed with dosimetry kits provided and evaluated by IRD/CNEN. The exposure time and voltage were measured using noninvasive detectors. The occupational dose was verified by thermoluminescent dosimeters. The existence of personal protection equipment, the type of image processing and knowledge of dentists about radiation protection were verified through the application of a questionnaire. Results Among the survey's results, it is important to emphasize that 90% of the evaluated equipments do not meet all the requirements of the Brazilian radiation protection standards. Conclusion The lack of knowledge about radiation protection, the poor operating conditions of the equipments, and the image processing through visual method are mainly responsible for the unnecessary exposure of patients to ionizing radiation.